Penerapan Algoritma Genetika untuk Optimasi Penjadwalan Pondok Pesantren berdasarkan Constraint Ustadz (Studi Kasus: Yayasan Pendidikan Budi Utomo, Gadingmangu, Perak, Jombang) - Huda Minhajur Rosyidin; Bayu Rahayudi; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Scheduling with a manual process will be less efficient because it takes a long time, problems in the preparation of the schedule become complex if the number of components increases or the size of each component increases. It is hoped that the resulting schedule will not only avoid clashes, but also adjust to the ustadz's constraints that must be met. Genetic Algorithm is an iterative, self-adjusting and probabilistic algorithm in the search for global optimization. The process of initializing the chromosomes by generating command data representing integers, where the command code entered for each gene is randomized. The chromosome with the highest fitness value is an illustration of the solution in this schedule. Based on the tests carried out,